Preadipocyte factor-1 concentrations in patients with anorexia nervosa: the influence of partial realimentation - Kaválková, P; Dostálová, I; Haluzíková, D; Trachta, P; Hanušová, V; Lacinová, Z; Papežová, H; Domluvilová, D; Zikán, V; Haluzík, M (Physiological research, 2012)
Preadipocyte factor-1 (Pref-1) is a member of epidermal growth-factor like family of proteins that regulates adipocyte and osteoblast differentiation. Experimental studies suggest that circulating Pref-1 levels may be also involved in the regulation of lipid and glucose metabolism and energy homeostasis. We hypothesized that alterations in Pref-1 levels may contribute to the ethiopathogenesis of anorexia nervosa or its underlying metabolic abnormalities. We measured Pref-1 concentrations and other hormonal, biochemical and anthropometric parameters in eighteen patients with anorexia nervosa and sixteen healthy women and studied the influence of partial realimentation of anorexia nervosa patients on these parameters. The mean duration of realimentation period was 46±2 days. At baseline, anorexia nervosa patients had significantly decreased body mass index, body weight, body fat content, fasting glucose, serum insulin, TSH, free T4, leptin and total protein. Partial realimentation improved these parameters. Baseline serum Pref-1 levels did not significantly differ between anorexia nervosa and control group (0.26±0.02 vs. 0.32±0.05 ng/ml, p=0.295) but partial realimentation significantly increased circulating Pref-1 levels (0.35±0.04 vs. 0.26±0.02 ng/ml, p<0.05). Post-realimentation Pref-1 levels significantly positively correlated with the change of body mass index after realimentation (r=0.49, p<0.05). We conclude that alterations in Pref-1 are not involved in the ethiopathogenesis of anorexia nervosa but its changes after partial realimentation could be involved in the regulation of adipose tissue expansion after realimentation.
Keywords: leptin; dospělí; tělesná hmotnost; index tělesné hmotnosti; membránové proteiny; Eating; Humans; Membrane Proteins; přijímání potravy; proteiny vázající vápník; mladý dospělý; Body Mass Index; tuková tkáň; Intercellular Signaling Peptides and Proteins; Calcium-Binding Proteins; Adipose Tissue; mužské pohlaví; Leptin; Adult; Anorexia Nervosa; Insulin; ženské pohlaví; mezibuněčné signální peptidy a proteiny; inzulin; lidé; Body Weight; mentální anorexie; Male; Young Adult; Female